Analysis Of The Causes Of PT. Bank Rabobank International Indonesia Stopped Operating - Girang Permata Gusti (Jurnal Manajemen dan Keuangan, 2019)
This paper tries to find out the cause of the stop of PT. Rabobank International Indonesia in terms of financial statements. Using descriptive research methods, case studies and document studies over a period of 10 years, starting from 2009 to 2018. The results of this study conclude that changes in the company's strategic focus that follow Rabobank Group's strategy are only serving customers from the food and agriculture sectors as one of the causes weakening of the company's financial performance.